A revolução pelos sentidos: traços surrealistas em A fúria do corpo, de João Gilberto Noll - Miguel Heitor Braga Vieira (Estudos de Literatura Brasileira Contemporânea)
This paper intends to relate João Gilberto Noll’s work, A fúria do corpo (1981), to the conception of surrealistic writing, surpassing the common ideas presented in the surrealistic movement as purposed by André Breton and his followers.